Climate Change and Nature Conservation in Britain and Ireland - Harrison, P (2001)
The study Modelling Natural Resource Responses to Climate Change (MONARCH) evaluates the impacts of climate change on wildlife and geomorphological features in Britain and Ireland. Climate change presents threats for some species, as well as opportunities for others. Below is a snapshot of the study findings. Introduction It identifies the potential implications for species and habitats in four environments: terrestrial, freshwater, coastal and marine. Winners and losers emerge, including some species threatened with national extinction. Climate is one of the key determinates of species’ distributions. As our climate changes, the distribution patterns of species and the composition of habitats will change. If we are to understand the likely changes and so assess the vulnerability of different species, as well as their ability to adapt, we need to understand how current patterns of distribution are related to our climate. This was the starting point for developing a bioclimatic classification for Britain and Ireland, demonstrating which parts of Britain and Ireland share the same climate characteristics now, before using models to predict future impacts on species. MONARCH identifies whether a suitable climate is likely to be available, but there is no guarantee that a species will be able to move to it. Climate will not be the only factor determining whether the new location is suitable. The ability to move and the ecological suitability of the new climate space will also be vital in determining the future distribution of species in Britain and Ireland. The study also indicates gaps in knowledge and the implications of the research findings for policy makers. The study, commissioned by a consortium of nature conservation organisations in Britain and Ireland, was carried out under the UK Climate Impacts Programme (UKCIP).